Cost analysis of severe burn victims in Southwest China: A 7-year retrospective study - Zeng, Zhuo; Li, Ning; Yang, Ling; Feng, Xue; Zuo, Fangqing; Luo, Gaoxing; Peng, Yizhi; Yuan, Zhiqiang (Frontiers in Public Health, 2023)
Background: Severe burn injury can be one of the most life-threatening pathologies, and always leads to considerable economic concerns. The purpose of the current study was to analyze the direct hospitalization costs of severe burn inpatients in Southwest China. Methods: Data related to all inpatients admitted with severe burns (total body surface area [TBSA] ≥30%) pooled from 2015 to 2021 were reviewed retrospectively at the Institute of Burn Research of Army Medical University. Demographic parameters, medical economic and clinical data were obtained from medical records. Results: A total of 668 cases were identified. The average age was 37.49 ± 21.00years, 72.3% were male. The average TBSA was 51.35± 19.49%. The median length of stay of inpatients in burn intensive care unit was 14 (interquartile range [IQR]: 5.0–34.8) days, and the median length of stay (LOS) was 41 (IQR: 22.0–73.8) days. The mortality was 1.6%. The median total cost was212,755.45 CNY (IQR: 83,908.80–551,621.57 CNY) per patient varying from 3,521.30 CNY to 4,822,357.19 CNY. The direct cost of scald burns was dramatically lower compared with that of other types of burns, with11,213.43 CNY to 2,819,019.14 CNY. The medical consumables presented the largest fraction of the total costs, with a median cost of 65,942.64 CNY (IQR: 18,771.86–171,197.97 CNY).The crucial risk factors for medical cost in our study were the TBSA, surgical frequency, LOS, depth of burn and outcome. Conclusions: We conclude that effective burn prevention program, shortening hospital stay, facilitating the healing of wound should be focused on to reduce the medical cost of inpatient with severe burn in tailored precautionary protocols.